A Computation Model of Micro-Blog Information Credibility Based on Bayesian Network - Rui, Haiyan; Zhao, Jiayue; Li, Chengcheng; Liu, Fengming (International Journal of Engineering and Technology, 2018)
With the rapid development, Microblog as an important interactive media, has become a kind of transmission carrier of the false information. Therefore, the research significance of Micro-blog information credibility becomes more and more important today. In this paper, different representative factors are selected from three facets--text contents, information dissemination and information source--which influence the information credibility of Micro-blog. We choose Netica software to build Bayesian network model and use the rumors grabbed from Sina Weibo as experimental data in order to get the relationship between conditions and phenomena from the changes of probability distribution in Bayesian network. On the basis of this, we find the influences of the representative factors on the subjective credibility of objective unreliable information.Â Â